2021
DOI: 10.3389/fgene.2021.595436
|View full text |Cite
|
Sign up to set email alerts
|

Association of CLDN6 and CLDN10 With Immune Microenvironment in Ovarian Cancer: A Study of the Claudin Family

Abstract: BackgroundThe claudin family is a group of transmembrane proteins related to tight junctions. While their involvement in cancer has been studied extensively, their relationship with the tumor immune microenvironment remains poorly understood. In this research, we focused on genes related to the prognosis of ovarian cancer and explored their relationship with the tumor immune microenvironment.MethodsThe cBioPortal for Cancer Genomics database was used to obtain the genetic variation pattern of the claudin famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Its expression is high in fetal tissues but absent in normal adult tissues. However, CLDN6 expression levels are often elevated in several types of human cancers, including testicular, ovarian, cervical, and lung adenocarcinomas . CLDN6 is a highly suitable target for tumor cells and is an ideal candidate for CAR-T therapy due to its consistent expression profile.…”
Section: Passive Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Its expression is high in fetal tissues but absent in normal adult tissues. However, CLDN6 expression levels are often elevated in several types of human cancers, including testicular, ovarian, cervical, and lung adenocarcinomas . CLDN6 is a highly suitable target for tumor cells and is an ideal candidate for CAR-T therapy due to its consistent expression profile.…”
Section: Passive Immunotherapymentioning
confidence: 99%
“…However, CLDN6 expression levels are often elevated in several types of human cancers, including testicular, ovarian, cervical, and lung adenocarcinomas. 102 CLDN6 is a highly suitable target for tumor cells and is an ideal candidate for CAR-T therapy due to its consistent expression profile. In a study, researchers found that CLDN6-CAR-T effectively eliminated CLDN6-expressing PA-1 ovarian cancers.…”
Section: Follicle-stimulating Hormone Receptor (Fshr)mentioning
confidence: 99%
“…Studies have shown that CLDN6 inhibits the development and progression in some cancers such as breast cancer [22,24,[61][62][63], cervical cancer [56], and meningioma [64]. In hepatocellular cancer [50,65,66], gastric cancer [52,67], endometrial cancer [68,69], and ovarian cancer [70], CLDN6 has the opposite roles. The oncogenic role or conversely tumor-suppressive effect of CLDN6 in different types of cancer is shown in Table 2.…”
Section: The Malignant Phenotypes Of Cldn6 Affected In Cancersmentioning
confidence: 99%
“… 14 , 15 In addition, CLDN6 has been found to be associated with immune infiltration in ovarian cancer. 16 However, the evidence linking CLDN6 to M2 macrophages in bladder cancer is still insufficient.…”
Section: Introductionmentioning
confidence: 99%